The Cutting Edge of Charcot Reconstruction: Anatomical Osteotomies Benchmarking Optimal Survivorship in Charcot Reconstruction - Raju Ahluwalia MBBS, MFSEM, FRCS (TrOrth); Firas Raheman MD(Res), MSc(Dist), MRCS; Peter Kosa MBBS; Ines Reichert MD, PhD, FRCS (TrOrth) (Foot & Ankle Orthopaedics, 2024)
Category: Diabetes; Midfoot/Forefoot Introduction/Purpose: Charcot neuroarthropathy is a debilitating condition that frequently leads to skeletal instability, deformity and an increased risk of ulceration leading to infection. This often necessitates prolonged periods of immobilization and casting. Nonetheless, opting for reconstruction presents an opportunity for limb preservation and the potential for weight-bearing functionality, contrasting starkly with the higher mortality rates associated with amputation. Methods: We present findings from a prospective study involving 102 patients who underwent Charcot reconstruction surgery conducted by two experienced surgeons from May 2014 to Oct 2024. Our approach incorporated advanced techniques such as 3D modeling and standardized osteotomies, including the King’s Cut and ARK osteotomy, to achieve precise anatomical corrections of Meary’s angle, as well as the anterior-posterior and lateral talo-calcaneal angles, along with calcaneal pitch. Additionally, patients underwent either primary or staged reconstruction in cases where osteomyelitis was suspected due to pre-existing ulceration. Definitive stabilization was achieved through internal fixation targeting the stabilization of unstable foot columns. A multivariate analysis was conducted to evaluate potential risk factors associated with failure, with statistical significance determined at P>0.05. Survivorship was defined by the absence of ulceration, catastrophic failure, or the necessity for amputation. Results: In the study, 79 feet were analyzed, with 46 undergoing single-stage and 43 two-stage reconstruction. Predominantly male (62.7%) with an average age of 56 years, most patients (89.63%) had type 2 diabetes, 56% hypertension, and 16% chronic kidney disease requiring dialysis. Among single-stage reconstructions, 52.1% had pre-operative ulcers, 13 ischemic heart disease, and 56 peripheral artery disease. 81% achieved normalized angles (P < 0.05); 3.4% required further surgery for infection, 17.9% experienced delayed wound healing. Survivorship rates were 98% at 3 years and 94% at 6 years, higher for those with vascular disease. At final follow-up, all maintained mobility, contributing to an overall 94.4% survivorship at 6 years, with 98% achieving ambulatory weight-bearing in shoes at 2 years. Conclusion: Strategic patient selection, multidisciplinary teamwork, and precise anatomic reconstruction, rather than merely achieving a plantigrade foot, are pivotal factors in achieving consistent and predictable outcomes for functional limb salvage. Research evidence underscores the importance of addressing pre-operative vascular compromise, as it significantly influences survivorship rates.